2011
DOI: 10.1038/ajg.2011.62
|View full text |Cite
|
Sign up to set email alerts
|

Successive Treatment With Cyclosporine and Infliximab in Steroid-Refractory Ulcerative Colitis

Abstract: In patients with intravenous steroid-refractory UC and who fail to respond to CYS or IFX, a second-line rescue therapy may be effective in carefully selected patients, avoiding colectomy within 2 months in two-thirds of them. The risk/benefit ratio should still be considered individually.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(56 citation statements)
references
References 27 publications
2
54
0
Order By: Relevance
“…The efficacy of calcineurin inhibitor and infliximab as salvage therapy was 75 (6/8) and 50% (4/8), respectively (p = 0.30). Several studies have reported on the efficacy and safety of infliximab as a rescue therapy for UC refractory to calcineurin inhibitor [9,10,11,12]. In each study, infliximab was deemed a successful rescue therapeutic option in patients with UC refractory to calcineurin inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of calcineurin inhibitor and infliximab as salvage therapy was 75 (6/8) and 50% (4/8), respectively (p = 0.30). Several studies have reported on the efficacy and safety of infliximab as a rescue therapy for UC refractory to calcineurin inhibitor [9,10,11,12]. In each study, infliximab was deemed a successful rescue therapeutic option in patients with UC refractory to calcineurin inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…But we don't have that freedom (Scotland governed by SMC) (245, 250) HP13 I'm not a massive NICE supporter but I actually think their guidance has been pretty sensible (346) HP13 they as a national body have to have their eye on healthcare costs and I think to favour the cheaper drug if in a situation where there is such a big difference between the 2 drugs is sensible, but also to acknowledge that it's not absolutely the right drug for everybody (429) HP14 I think the current NICE guidelines are um, a bit tricky because I think if you are going to give a patient infliximab you need to give them ., and then they respond to it, if they do respond to it you want to be able to continue the treatment and I think it may have more of a long term use than the NICE guidelines that we're currently using (38) HP14 I think it's unduly restrictive and I think it will eventually change. I think it's actually quite hard to adhere to actually as well.…”
Section: Excellentmentioning
confidence: 99%
“…We used the electronic search strategies checklist of the Cochrane Collaboration. 31 We identified nine observational studies and one RCT [32][33][34][35][36][37][38][39][40][41] that compared the efficacy and safety of ciclosporin with those of infliximab ( Table 1). Although both ciclosporin and infliximab were effective in steroid-resistant UC, results did not agree which drug was better.…”
Section: Review Of Literaturementioning
confidence: 99%
“…There have been some reports of switching from ciclosporin to infliximab and vice versa if one treatment is not effective. [24][25][26][27] However, higher rates of adverse events and mortality due to long-term stronger immunosuppression have warned that administering the sequential therapy should be carefully decided on an individual basis. If we could predict the efficiency of the individual treatment for severe refractory UC with high accuracy, an early clinical decision-making would be made and ineffective medications would be avoided before patients undergo long-term stronger immunosuppression.…”
Section: Resultsmentioning
confidence: 99%